(untitled) (International Journal of Innovative Research in Engineering & Management, 2022)
There is no denying fiber reinforced concrete’s (FRC) value in a variety of civil engineering applications. A wide variety of applications, including slabs on grade, architectural panels, precast goods, offshore buildings, structures in seismic zones, thin and thick repairs, crash barriers, footings, hydraulic structures, and many more, have successfully used fiber reinforced concrete to date. As a practical means of enhancing concrete’s performance, Fiber Reinforced Concrete (FRC) is gaining popularity. Now, fibers are being specified for use in concrete slabs, pads, loading docks, thin unbonded overlays, tunnels, bridge decks, and pavements. These applications of fiber-reinforced concrete are getting more and more well-liked and function exceptionally well. Concrete with fibrous reinforcement, or fiber-reinforced concrete (FRC), has a higher structural integrity. Short, isolated fibers that are evenly spaced out are present.